Current State and New Trends in the Use of Cellulose Nanomaterials for Wastewater Treatment - Abouzeid, Ragab E; Khiari, Ramzi; El-Wakil, Nahla; Dufresne, Alain (Biomacromolecules, 2019)
Nanotechnology has been identified as having great potential for improving the efficiency of water prevention and purification while reducing costs. In this field, two applications of nanocellulose have generated attention and have proven to be a sound strategy as an adsorbent and as a membrane for the removal of contaminants. This potential is attributed to its high aspect ratio, high specific surface area, high capacity retention, and environmental inertness. In addition to the aforementioned advantages, the presence of active sites allows the incorporation of chemical moieties that may enhance the binding efficiency of pollutants to the surface. This review paper intends to understand how nanocellulose affects the adsorption behavior of water pollutants, e.g., heavy metal ions, microbes, dyes, and organic molecules, and is divided in two parts. First, a general overview of the different strategies for the preparation of nanocellulose is described, and its specific properties are reported. The second section reports some of its application as adsorbent nanomaterial or separation membrane. It appears that the use of nanocellulose for these applications is very promising for wastewater treatment industries.